Radiotherapy combined with immune checkpoint inhibitors in locally advanced/metastatic esophageal squamous cell carcinoma: clinical trials, efficacy and future directions - Jiang, Mengjie; Hu, Yujie; Lin, Gang; Chen, Chao; Li, Huafeng (Frontiers in Immunology, 2023)
Esophageal squamous cell carcinoma (ESCC) is a common malignancy worldwide and often diagnosed at advanced stages with poor prognosis. Combination of radiotherapy and immunotherapy seems to be a promising approach for treating ESCC. This comprehensive review article summarizes the current state of combination of radiotherapy and immunotherapy in locally advanced/metastatic ESCC, delineates the clinical trials that merit attention, and outlines unresolved issues and future research directions in this field. The clinical trial findings suggest that radio-immunotherapy combination may improve tumor response and overall survival with manageable side effects, highlighting the importance of patient selection and the necessity for further research to optimize treatment strategies. Issues such as irradiation dosage, fractionation regimen, irradiation site and technique of radiotherapy, as well as the timing, sequence and duration of combination therapy will all affect treatment outcomes, justifying further in-depth investigation.